Susceptibility of Porphyromonas Gingivalis Isolated from Patients Suffering from Periodontitis to Antibiotics - Mohammed Oudah Hamad (Journal of Global Pharma Technology, 2018)
Twenty three of P. gingivalis isolated from ninety one patients complaining from periodontitis with different age from both gender in Babylon city. According to routine culture methods were done using differential media, anaerobic condition and morphological criteria such as microscopically and biochemically testsand percentage (25.3%). The activity of 27 antibiotics were tested towards the current isolates, and the results showed high degree of resistance for most antibiotics represented by: penicillin, ampicillin, amoxicillin ,carbenicillin, , tetracycline, doxycycline (100%), ticarcillin(92.6%) ,piperacillin (95.7%),erythromycin (85.2%) ,Co-trimoxazole and chloramphenicol (81.5%),cefepime (63.0%), cefixime ,ampiclox ,colistin(51.9%), ciprofloxacin and norfloxacin (56.5%), tobromycin (52.1%), ceftrixzone, aztreonam (47.8%), azithromycin, gentamicin and cefotaxime (44.4%) amoxiclave (37.1%),amikacin (33.3%),while The meropenem and impinem showed more effective against current isolates .The present results were consistent the what is known multidrugresistant P.gingivalis.The minimum inhibitory concentrations (MIC) of most present isolates were higher.Keywords: P.gingivalis, Periodontitis, Antibiotics resistance, Minimum inhibitory concentration.